Alkyl Carbon–Carbon Bond Formation by Nickel/Photoredox Cross‐Coupling. Issue 19 (27th February 2019) - Milligan, John A.; Phelan, James P.; Badir, Shorouk O.; Molander, Gary A.
Abstract: The union of photoredox and nickel catalysis has resulted in a renaissance in radical chemistry as well as in the use of nickel‐catalyzed transformations, specifically for carbon–carbon bond formation. Collectively, these advances address the longstanding challenge of late‐stage cross‐coupling of functionalized alkyl fragments. Empowered by the notion that photocatalytically generated alkyl radicals readily undergo capture by Ni complexes, wholly new feedstocks for cross‐coupling have been realized. Herein, we highlight recent developments in several types of alkyl cross‐couplings that are accessible exclusively through this approach. Abstract : Nickel in the limelight : Nickel/photoredox dual cross‐coupling is a rapidly developing method that enables alkyl carbon–carbon bond formation. This Minireview discusses the progress of this field by highlighting various types of bond formations that have recently been developed.